The Usage of Biofeedback Techniques at Schools In the District of Maran to Invervene Drugs Abuse and Diciplinary Cases - Muhammad Nubli, Abdul Wahab; Nazrolnizah, Mohamad Noorzeli; Azham, Abdul Rahman (2016)
Biofeedback techniques have been identified to be able to detect emotional disorders and provide intervention for the disorder. This program was being introduced to provide knowledge and skills to the school counselors on the use of Biofeedback equipment, protocols and Biofeedback intervention to help high school students who have been identified as abusing drugs and involved in disciplinary misconducts to recover from the problems. The program started by developing the use of Biofeedback protocol, module development and the acquisition of Biofeedback equipment. A total of 19 schools with 39 teachers and 165 students have been involved with this project. As a result of the program, it has been found that all the four project objectives have been achieved. 80% of the teachers who were involved in this project were able to use the biofeedback devices; they were also capable to use biofeedback protocol which was being developed. About 84% of the students who received guidance from the teachers were able to change the status of coherence score of the heart rate variability. 38% of the students were able to improve their academic performance and 66% of them were able to improve their behaviours. The results of this project had an impact on schools in which teachers were capable in improving counseling sessions through Biofeedback techniques. Students involved were also able to make changes to their attitudes. It is hoped that this project would continue and students would master the knowledge and skills gained through the implementation of this project.